Group or individual lifestyle-integrated functional exercise (LiFE)?: a qualitative analysis of acceptability - Reicherzer, Leah; Kramer-Gmeiner, Franziska; Labudek, Sarah; Jansen, Carl-Philipp; Nerz, Corinna; Nystrand, Malin J.; Becker, Clemens; Clemson, Lindy; Schwenk, Michael (BMC geriatrics, 2021)
The Lifestyle-integrated Functional Exercise (LiFE) program is an effective but resource-intensive fall prevention program delivered one-to-one in participants’ homes. A recently developed group-based LiFE (gLiFE) could enhance large-scale implementability and decrease resource intensity. The aim of this qualitative focus group study is to compare participants’ experiences regarding acceptability of gLiFE vs LiFE.